Archaeometric characterization of pottery from the Iron Age hillfort of Pintia (Valladolid, Spain). (February 2022) - Coria-Noguera, José Carlos; Badreshany, Kamal P.; Sanz Mínguez, Carlos
Highlights: Extensive archaeometric dataset of Vaccean and Roman pottery from the site of Pintia (Spain). Ceramics locally made with broad continuity after the Roman conquest despite political changes. Non-calcareous raw materials were preferred and used for different styles and colours. Vaccean and Roman period ceramics are petrographically similar but show chemical differences. Chemistry indicates a shift in clay sources utilised during the Roman period. Abstract: This paper presents the results of an archaeometric analysis of pre-Roman and Roman ceramics from the Vaccean Iron Age hillfort of Pintia (Valladolid, Spain). The study assesses degrees of romanization and hybridization by investigating changes in local ceramic production and the dissemination of new technologies with the arrival of Roman rule. Thin-section petrography, XRD, and geochemical analyses (using XRF) have been utilised on a selection of pre- and post-conquest vessels from habitation contexts. This work goes beyond traditional typological analyses to shed light on the resilience of 'Second Iron Age' communities, who's ceramic traditions largely persist into Roman times, albeit with some changes, like shifts in the preferences and location of raw materials.